Utilization of pine tree biochar produced by flame-curtain pyrolysis in two non-agricultural applications. (February 2020) - Kalderis, Dimitrios; Tsuchiya, Shion; Phillipou, Katerina; Paschalidou, Polyxeni; Pashalidis, Ioannis; Tashima, Daisuke; Tsubota, Toshiki
Abstract: Main objective of this work was to demonstrate the applicability of biochars obtained from pine tree residues through low cost, easy to operate, flame-curtain pyrolysis, in two distinctively different applications. In the first application, it was shown that base-oxidized pine tree biochar had an excellent adsorption behavior towards U(VI) in aqueous solutions, achieving a qmax value of 800 mg g − 1 . It was also demonstrated that surface interactions with biochar's oxygen-containing groups dominated over physical interactions with the pore structure. In the second application, KOH-activated pine tree biochar showed a very promising behavior as an electrode material in an electron double-layer capacitor. Due to its high surface area (2500 m 2 / g), capacitance values of 190 F g − 1 at 10 mA g − 1 for discharge process were achieved. As a conclusion, it was shown that flame-curtain pyrolysis biochars are suitable for non-agricultural applications, in the cases where soil application is not an option. Highlights: Low-technology pyrolysis can produce high-added value biochars for non-agricultural applications. Base-oxidized pine tree biochar showed excellent adsorption behavior towards U(VI). KOH-activated biochar can be a promising candidate as an EDLC electrode material.